2023
DOI: 10.3390/ijerph20021472
|View full text |Cite
|
Sign up to set email alerts
|

Digital Trends, Digital Literacy, and E-Health Engagement Predictors of Breast and Colorectal Cancer Survivors: A Population-Based Cross-Sectional Survey

Abstract: Introduction: Advances in information and communication technology (ICT) and post-COVID-19 tectonic changes in healthcare delivery have made it possible for cancer survivors to obtain disease-related information for remote management online rather than through healthcare providers. To comprehend and evaluate health information, digital literacy is crucial. Objectives: This study examined cancer survivors’ information-seeking behaviour, information sources, digital health literacy, and digital trends, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 58 publications
1
23
0
Order By: Relevance
“…The format used enabled them to exchange ideas and generated meaningful discussions ( 28 , 29 ). The FGs were carried out as a follow-up to a previous study, which showed that DHL was the only independent predictor of eHealth app use and information receptivity among CRC survivors ( 15 ). In addition, previous work identified that CRC survivors' age as an independent factor in determining their use of online information ( 4 ).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The format used enabled them to exchange ideas and generated meaningful discussions ( 28 , 29 ). The FGs were carried out as a follow-up to a previous study, which showed that DHL was the only independent predictor of eHealth app use and information receptivity among CRC survivors ( 15 ). In addition, previous work identified that CRC survivors' age as an independent factor in determining their use of online information ( 4 ).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the digitalization of healthcare systems brought digital health literacy “DHL” as a new dimension of HL. “eHealth literacy” evolved into “digital health literacy” and is now used interchangeably ( 14 , 15 ). In 2006, Norman and Skinner ( 14 ) defined eHealth literacy as the ability to search, receive, comprehend, and evaluate health information online to solve health issues ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations